Relevant parameters on the energy efficiency of closed refrigerated multideck display cases - Heidinger, Gustavo Galdi (2016)
The application of closed refrigerated multideck display cases (CRDC) and electronic fans is slowly increasing in Brazilians supermarkets, following the international trend. In order to obtain energy savings, this paper reports the results of experimental tests performed in a CRDC according to ISO 23953 to evaluate the influence of (1) environmental conditions, (2) gaps between doors and (3) fans type on the overall performance of a display case. Experimental laboratory tests were performed on two different conditions of temperature and relative humidity of the ambient air (Tamb=25°C; amb=60% and Tamb=27°C; amb=70%), with electromagnetic and electronic fans, and with and without gaps between doors. The analysis and discussion of experimental results include the comparison of compressor energy consumption, total heat load, total condensed water collected on defrost periods and air and product temperatures. The experimental data analysis provides valuable information to set the operative parameters of the CRDC taking into account usual in-store conditions in Brazil.